Immunohistochemical evaluation of epidermal proliferation, differentiation and melanocytic density in symmetrical acrokeratoderma. (22nd May 2017) - Yang, P.‐P.; Peng, J.; Wu, Y.‐Y.; Liu, Z.; Sheng, P.; Zhou, Y.; Li, S.‐J.; Fan, Y.‐M.
Summary: Background: Symmetrical acrokeratoderma (SAK) is characterized by brown to black hyperkeratotic patches on acral regions. Although epidermal hyperkeratosis and acanthosis are consistent pathological changes, the nature of epidermal hyperplasia is unknown. Aim: To evaluate epidermal proliferation and differentiation and melanocytic density in skin lesions of SAK. Methods: Expression of keratin 10 (K10), K14, K16, involucrin, filaggrin, Ki‐67, and Melan‐A was detected by immunohistochemistry in eight patients with SAK, seven patients with ichthyosis vulgaris (IV) and six healthy controls (HCs). Results: Expression of K14, K16, involucrin and filaggrin was upregulated in patients with SAK compared with patients with IV and the HCs ( P < 0.01–0.05), but K10 expression was similar for the three groups ( P > 0.05). Numbers of Ki‐67+ and Melan‐A+ cells were higher in patients with SAK than in patients with IV and the HCs ( P < 0.05). Conclusions: These results demonstrate that excessive keratinocyte proliferation and abnormal differentiation contribute to epidermal hyperplasia, while melanocytic proliferation is responsible for the pigmented lesions in SAK.